Chest wall myoblastoma - Delbene, Roberto; Chifflet, Juan; Fernández, Isabel; Bertullo, Hugo; Martínez, José Luis (Cirugía del Uruguay, 1986)
A case of soft tissue tumor of the thoracic wall is presented. In spiteof belng classified among sarcomas, their local aggre siveness and !he exceptional cases when metasla ize, keep them apart fror other sarcomas. The therapeu!íc approach is different to most part of sarcomas.